1990
DOI: 10.1007/bf00431359
|View full text |Cite
|
Sign up to set email alerts
|

Pathological alterations in human tendons

Abstract: The present authors analyzed the pathological alterations of 1966 tendons examined in the National Institute of Traumatology, Budapest, during the past 18 years. The majority of cases proved to be tendinopathies (hypoxic-degenerative tendinopathy or calcific tendinitis, tendolipomatosis and mucoid degeneration) leading to tendon rupture. The incidence of tendon tumors, foreign bodies, infectious tendon diseases, and other pathological conditions was clearly lower. The methods of tissue preparation and of exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 12 publications
4
31
0
Order By: Relevance
“…Postmortem studies revealed a prevalence of Achilles tendon degeneration ranging from 15% to 35%. 24,25 The absence of demonstrable vascularity on color Doppler imaging in healthy tendons is consistent with previous studies. 9,10,26 In current practice, there are several sonographic findings that may suggest a diagnosis of tendinopathy, including increase in tendon caliber, altered fibrillar echotexture, and increased tendon vascularity.…”
Section: Discussionsupporting
confidence: 91%
“…Postmortem studies revealed a prevalence of Achilles tendon degeneration ranging from 15% to 35%. 24,25 The absence of demonstrable vascularity on color Doppler imaging in healthy tendons is consistent with previous studies. 9,10,26 In current practice, there are several sonographic findings that may suggest a diagnosis of tendinopathy, including increase in tendon caliber, altered fibrillar echotexture, and increased tendon vascularity.…”
Section: Discussionsupporting
confidence: 91%
“…A 1990 study by Jozsa used polarization and electron microscopy to study the histological changes found in injured tendons (69). Most common were hypoxic-degenerative tendinopathy, tendolipomatosis infiltrate, mucoid degeneration, and calcific tendinitis.…”
Section: Mechanical Behavior Of Tendonsmentioning
confidence: 99%
“…An increased content of type III collagen in the fibers would tend to reduce their tensile strength (Jozsa et al, 1984;Jozsa et al, 1990;Maffulli et al, 2000;Matthew & Moore, 1991). ACS-treated animals showed markedly more mature, thick reddish/orange collagen fibers at weeks 2 and 8 postoperatively as compared with controls and quantitative evaluation of collagen type III showed a three fold reduced level of this collagen at weeks 1, 2 and 8.…”
Section: Autologeous Conditioned Serummentioning
confidence: 99%